ß-hydroxy ß-methylbutyrate (HMB) supplementation effects on body mass and performance in elite male rugby union players - McIntosh, N. D.; Love, T. D.; Haszard, J.; Osborne, H.; Black, K. E. (The Journal of Strength and Conditioning Research, 2018)
Preseason is characterized by high training volumes with short recovery periods ß-hydroxy ß-methylbutyrate (HMB) has been postulated to assist with recovery. ß-hydroxy ß-methylbutyrate has been shown to improve strength and body composition among untrained groups; the benefits of HMB among trained populations are unclear because of the methodologies employed. This randomized control trail determined the effects of 11 weeks HMB supplementation on body mass and performance measures in 27 elite rugby players. ß-hydroxy ß-methylbutyrate group (n = 13), mean ± SD age 20.3 ± 1.2 years, body mass 99.6 ± 9.1 kg; placebo group (n = 14), age 21.9 ± 2.8 years body mass 99.4 ± 13.9 kg for placebo. During the supplementation period, body mass increased with HMB 0.57 ± 2.60 kg but decreased with placebo 1.39 ± 2.02 kg (p = 0.029). There were no significant differences in any of the 4 strength variables (p > 0.05). However, on the yo-yo intermittent recovery test (YoYo IR-1), the placebo group improved 4.0 ± 2.8 levels but HMB decreased 2.0 ± 3.0 levels (p = 0.003). The results of this study suggest that HMB could be beneficial for gaining or maintaining body mass during periods of increased training load. However, it appears that HMB may be detrimental to intermittent running ability in this group although further research is required before firm conclusions can be made. Only 6 participants on HMB managed to complete both YoYo IR-1 tests because of injury, a larger sample size is required to fully investigate this potentially negative effect. Further, the mechanisms behind this decrement in performance cannot be fully explained and requires further biochemical and psychological investigation.